2017
DOI: 10.20944/preprints201701.0102.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Facial Expression Recognition with Fusion Features Extracted from Salient Facial Areas

Abstract: Abstract:In pattern recognition domain, deep architectures are widely used nowadays and they have achieved fine grades. However, these deep architectures need special demands, especially big datasets and GPU. Aiming to gain better grades without deep networks, we propose a simplified algorithm framework using fusion features extracted from the salient areas of faces. Furthermore, the proposed algorithm has achieved a better result than some deep architectures. For extracting more effective features, this paper… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The accuracy of the basic CNN algorithm using only the static feature was 84.48%. Liu et al [62] proposed a method to extract features of salient areas by using LBP and HOG features with gamma correction, which resulted in 90% accuracy. Goyani and Patel [63] used feature vectors by constructing the Haar wavelet of multiple levels with the face, eyes, and mouth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy of the basic CNN algorithm using only the static feature was 84.48%. Liu et al [62] proposed a method to extract features of salient areas by using LBP and HOG features with gamma correction, which resulted in 90% accuracy. Goyani and Patel [63] used feature vectors by constructing the Haar wavelet of multiple levels with the face, eyes, and mouth.…”
Section: Resultsmentioning
confidence: 99%
“…In the future, we will continue to study and analyse the problem of FER, and expect to find better rules and strategies for superior performance. Table 4 Comparisons between our method and the state-of-the-arts FER algorithms on the JAFFE dataset Method Accuracy CNN [62] 84.48 salient feature [63] 90.00 multi-level Haar wavelet [64] 90.56 hierarchical deep learning method [58] 91.27 MCCNN [65] 95.80 Ms-RAN (ours) 96.03…”
Section: Resultsmentioning
confidence: 99%
“…Ryu et al used a coarse grid for stable codes (highly related to nonexpression), and a finer one for active codes (highly related to expression) as the features for facial expression recognition [ 20 ]. Liu et al extracted LBP and HOG features from the salient areas that were defined on the faces; then Principal Component Analysis (PCA) is used to reduce the dimensions of the features which fused with LBP and HOG [ 21 ]. Ghimire et al divided the whole face region into domain-specific local regions; then region-specific appearance features and geometric features are extracted from the domain-specific regions for facial expression recognition [ 22 ].…”
Section: Related Workmentioning
confidence: 99%
“…Liu et al [52] suggested a simple framework algorithm to extract facial features from the salient face area. The proposed algorithm normalises the salient features to the same size and extracts similar face features of different subjects.…”
Section: Feature Extraction Techniquesmentioning
confidence: 99%
“…SVM [41, 47, 48, 52, 53, 56, 58] is a well‐known supervised classification algorithm and also called a maximum margin classifier [61]. The hyperplane is selected with higher margin to discriminate two classes in n ‐dimensional space.…”
Section: Frequently Used Classifiers and Datasetsmentioning
confidence: 99%